Biochemistry - Pelley, John W.; Goljan, Edward F.; Pelley, John W. (Philadelphia, PA Mosby/Elsevier, 2011)
Get the most from your study time, and experience a realistic USMLE simulation with the 3rd Edition, by Drs. John W. Pelley, and Edward F. Goljan. This new reference in the highly rated Rapid Review Series is formatted as a bulleted outline with photographs, tables, and figures that address all the biochemistry information you need to know for the USMLE. And with Student Consult functionality, you can become familiar with the look and feel of the actual exam by taking a timed or a practice online test that includes 350 USMLE-style questions.
Carbohydrates, lipids, and amino acids : metabolic fuels and biosynthetic precursors -- Proteins and enzymes -- Membrane biochemistry and signal transduction -- Nutrition -- Generation of energy from dietary fuels -- Carbohydrate metabolism -- Lipid metabolism -- Nitrogen metabolism -- Integration of metabolism -- Nucleotide synthesis and metabolism -- Organization, synthesis, and repair of DNA -- Gene expression -- DNA technology -- Common laboratory values.
Includes index.
Revised edition of: Biochemistry. 2nd ed. ©2007.
Keywords: Biochemistry -- Outlines, syllabi, etc; Biochemistry -- Examinations, questions, etc